Graph-Based Resource Allocation for D2D Communications Underlying Cellular Networks in Multiuser Scenario - Bin Guo; Shaohui Sun; Qiubin Gao (International Journal of Antennas and Propagation)
With the characteristics of considerable user equipment, massive traffic and numerous local services, but limited frequency resources, the mobile communications in the future require efficient use of frequency resources. Device-to-device (D2D) communications underlying cellular networks have been considered as a promising solution to improve the resources utilization in local scenario. In this paper, we investigated the resources allocation problem in multiuser scenario and proposed a graph-based resources allocation scheme which can achieve suboptimal performance but with low computational complexity and less feedback information.